MENARIK BANDUL KEKUASAAN KE TITIK EQUILIBRIUM: POPULISME SEBAGAI TANTANGAN DAN PELUANG BAGI SISTEM PRESIDENSIAL DI INDONESIA - T.R., Muhammad Ridha (Prodi Ilmu Pemerintahan FISIP UNIBBA, 2019)
Indonesian Presidential system is a system of government that is very complex and complicated, which makes it appear to be a unique in studies about the system and can enrich the wealth of political science. Presidential system in Indonesia is seen as a unique, if not referred to as the strangeness-as formed above a lot of the principles that characterized the parliamentary system as a multiparty system adopted in the party system in Indonesia, which then implies the existence of a coalition government, both executive and legislature. this then led to the imbalance of power between the executive and the legislature, wich the pendulum of power should be at the point of equilibrium, but in reality it was the pendulum of power in the hands of legislative favors (heavy legislative) This paper attempts to look at the phenomenon of populism as the opportunities and challenges for Indonesia's presidential system. This paper see the presidential’s problems from the standpoint of not only the president as an institution, but also the legislative. Thesis statement of this paper is that one of the major problems faced by Indonesia's presidential system is not only the weakness of the president, but also a system of representation there. Because if we look at the phenomenon of populism where more people rely expectations, demands, and desires at a figure that is considered a populist, then all efforts toward equilibrium pendulum returns this instead of creating a mechanism of checks and balances, but it will be a way for the emergence of a new authoritarian or at least reduce the democratic values.